Peningkatan Hasil Belajar Peserta Didik Kelas VII SMP Negeri 2 Tarutung Melalui Model Pembelajaran Problem Based Learning pada Pembelajaran Pak - Santi Aritonang; Afiliasi Penulis (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This Classroom Action Research aims to improve the learning outcomes of class VII students in the Catholic Religious Education subject at SMP Negeri 2 Tarutung. There were 1 female and 7 male students who were research subjects in an effort to implement a problem-based learning model (Problem Based Learning). The research results showed that there was a significant increase in student learning outcomes after implementing the PBL learning model. In cycle I, the average student score was 71.25 with an achievement category of 2 adequate students and 6 proficient students. This indicates that there are still some students who have not achieved the expected competency. By implementing PBL more intensively and providing more targeted guidance, student learning outcomes have increased quite significantly. In cycle II, the average student score increased to 87.50 with the achievement category being 2 proficient students and 6 proficient students. This increase in learning outcomes shows that the PBL learning model is effective in increasing students' understanding of the Catholic Religious Education material I Have the Capabilities.